1994
DOI: 10.1016/0009-2614(94)00007-7
|View full text |Cite
|
Sign up to set email alerts
|

The microwave spectrum of cyclopropane · ammonia. A novel structure for cyclopropane complexes

Abstract: The microwave spectrum of the cyclopropane-ammonia (CsHs* 14NHs) complex has been observed using a pulsed nozzle, Fourier-transform microwave spectrometer. The spectrum is characteristic of a symmetric top, IS,,= 2668.7 16 l(4), with free internal rotation of the NHs subunit. The spectra of the CsHs*r5NHs, CsDs*r5NHs, and CSHe*'4NDs isotopomers were also measured. This gives a structure in which the nitrogen of the ammonia interacts with the top of the cyclopropane ring, resulting in a stacked structure with R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“… a Values obtained from ref . b PA is the proton affinity of the free amine monomer in units of kcal/mol obtained from ref .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… a Values obtained from ref . b PA is the proton affinity of the free amine monomer in units of kcal/mol obtained from ref .…”
Section: Discussionmentioning
confidence: 99%
“…Little work has been done on complexes of cyclopropane with non-hydrogen donor moieties. Recently, however, we found a new structure for cyclopropane complexes with the study of the cyclopropane−ammonia complex . The structure of CYC·NH 3 is stacked with the lone pair of the nitrogen atom pointing toward the center of the cyclopropane ring.…”
Section: Introductionmentioning
confidence: 99%
“…Complexes of cyclopropane ( 1 ) with various electrophiles and nucleophiles exhibit unusual molecular structures ( 2 − 4 ). Computations on corner- ( 2a-asym C s , 2a-sym C s ) and edge-protonated cyclopropane ( 3a , C 2 v ) reveal an extremely flat potential energy surface . The ability of cyclopropanes to participate as hydrogen-bonding proton acceptors, first demonstrated inter- and intramolecularly by Schleyer et al using IR spectroscopy, has been confirmed recently by MW spectroscopy. Like the π-systems in unsaturated hydrocarbons, the cyclopropane “bent bonds” 7 act (edge coordination mode 3 ) as proton acceptors for HOR, H 2 O, HF, HCl, and HCN .…”
Section: Introductionmentioning
confidence: 98%
“…The breaking of hydrogen bonds between water molecules by cyclopropane ( 1 ) is said to be responsible for the anaesthetic activity of 1 . However, in weaker van der Waals complexes, NH 3 , HNMe 2 , and NMe 3 10 are located above the cyclopropane ring plane (face coordination mode 4 ).
…”
Section: Introductionmentioning
confidence: 99%
“…The forces of the intermolecular and intramolecular hydrogen bonds may ensure that there is no free rotation around the N–C(α) bond. The gas phase rotation barrier (≈10–15 kJ/mol) of amine group is much lower than the rotation barrier in solids (≈20–60 kJ/mol) . In solids, the rotation energy barrier is the energy to break the hydrogen bonds with very little rearrangements .…”
Section: Resultsmentioning
confidence: 95%